Analisis Frekuensi dan Bentuk Letupan Gunung Lumpur Bleduk Kuwu - Fita Widiyatun (Universitas Indraprasta PGRI Jakarta, 2017)
Bleduk Kuwu is one of the many mud volcanoes in Indonesia are still active from the past to the present. Location of Kuwu Bleduk in Purwodadi, Grobogan, Central Java. Bleduk Kuwu is a tourist attraction that has eruption around 7-15 times per minute. The purpose of this research was to determine the various forms of the eruption that occurred in Bleduk Kuwu, large of diameter eruptions, and frequency. Data is collected on September 30, 2013, during 47 minutes and 27 seconds. The tools used in data collection are three seismometers TDV23s short feedback period of three components and a camcorder. The results of video analysis, there are four types of eruptions that occurred in Bledug Kuwu. The eruption mode is a powerful eruption, row eruption, double eruption, and regular eruption. Each of the eruption has varying diameters. Size of the largest eruption diameter is (3.1 ± 0.1) m and the frequent diameter eruptions around (1.0 - 2.0) m. Analysis of seismic signals, obtained an eruption frequency is (1.6 to 4.2) Hz with the dominant frequency of 2.0 Hz.